The Effectiveness of Content Marketing in Building Brand Awareness - Wei, Zhang; Hina, Hermyn Benny; Jiao, Deng; Yudilestari, Eka Putri; Hamka, Hamka (Journal Markcount Finance, 2024)
In the internet era, content marketing has become the main strategy for increasing brand awareness. This research looks at how effective content advertising is in increasing consumer awareness of brands and their impact on target audiences. Research shows that personalized and planned content marketing can significantly increase consumer knowledge about a brand. Compelling and engaging content not only grabs the audience's attention, but also increases the likelihood of them sharing, naturally increasing brand reach. Additionally, proper platform usage and consistent messaging are critical to the effectiveness of content advertising. However, quality content and the right distribution strategy are essential for effective content marketing. This study also found problems in content marketing such as measuring ROI and audience engagement. Good content can increase brand awareness, but it's important to create clear metrics and useful analytical tools to assess the success of the campaign. This allows businesses to change their plans based on the results they obtain. Overall, with the right strategy and measurements, content marketing is a powerful tool for increasing brand awareness. Companies can increase their brand visibility and reach target audiences more effectively by optimizing content quality, selecting appropriate distribution channels, and conducting careful evaluations.